IMPLEMENTATION OF THE FULFILLMENT OF CHILD SUPPORT AFTER DIVORCE AT THE SUKADANA RELIGIOUS COURT OF LAMPUNG PROVINCE (Sociology of Law Perspective) - Rachman, Evy Septiana; Zuhraini, Z.; Jayusman, J.; Mahmudah, Siti (Universitas Islam Negeri Raden Intan Lampung, 2022)
Child support is an obligation that arises because of the marriage bond. A father is obliged to meet the needs of the child's life until adulthood, even if there is a divorce. However, at the Sukadana Religious Court, this did not happen, there were still many fathers who neglected to provide for their children after the divorce decision was made. This is what becomes interesting for further research using the empirical legal approach method, data collection methods using interviews and documentation. This study will analyze the perspective of the sociology of law and draw conclusions using inductive and deductive thinking frameworks. The results of this study indicate that there are still children whose livelihood rights are not fulfilled in accordance with what has been stipulated in the decision of the Sukadana Religious Court. The father only carries out his obligations a few times in providing a support for the child and the amount given is not in accordance with what is stipulated in the court decision. This happens due to two factors: internal factors and external factors. So that this causes the ineffectiveness of implementing laws and regulations related to children's livelihoods.